2021
DOI: 10.1097/mao.0000000000003353
|View full text |Cite
|
Sign up to set email alerts
|

Cochlear Implantation in Children with Autism Spectrum Disorder: A Systematic Review and Pooled Analysis

Abstract: Objective: To determine outcomes following cochlear implantation (CI) in children with autism spectrum disorder (ASD). Databases Reviewed: MEDLINE, Embase, Web of science, Cochrane Library, and Clinicaltrial.gov. Methods: The review was performed according to the PRISMA statement. Primary outcomes measures were changes in speech perception and speech production scores. Secondary outcome measures included communication mode, device use, parental recommendation of implant, postoperative hyperacusis, and quality … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
19
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(23 citation statements)
references
References 47 publications
0
19
0
Order By: Relevance
“…The link between hearing loss and ASD, however, has sparse evidence to support it. Some studies estimate the hearing loss in ASD to be ten times higher than in the neurotypical population, others documenting similar rates 3 . Some of the stereotypical signs of autism, for example, toe walking, hand flapping or 'sustained odd play' can result in an earlier diagnosis, but it has been shown that if a child has a hearing impairment, this can delay the diagnosis of autism 38 .…”
Section: Asd and Hearing Lossmentioning
confidence: 99%
See 4 more Smart Citations
“…The link between hearing loss and ASD, however, has sparse evidence to support it. Some studies estimate the hearing loss in ASD to be ten times higher than in the neurotypical population, others documenting similar rates 3 . Some of the stereotypical signs of autism, for example, toe walking, hand flapping or 'sustained odd play' can result in an earlier diagnosis, but it has been shown that if a child has a hearing impairment, this can delay the diagnosis of autism 38 .…”
Section: Asd and Hearing Lossmentioning
confidence: 99%
“…A review article 3 , showed that out of the 9 studies analysed, 8 demonstrated that autistic children had an overall improvement in their speech expression following cochlear implantation, although the extent of this was highly variable. It was also concluded that, in general, non-compliance was usually related to the severity of ASD 3 .…”
Section: Asd and Cochlear Implantationmentioning
confidence: 99%
See 3 more Smart Citations